2011
DOI: 10.3109/14767058.2011.566768
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum 25(OH)D levels in the third trimester of pregnancy during the winter season

Abstract: This study showed a remarkable high rate of vitamin D deficiency in pregnant women during the winter season and we have found high levels of vitamin D in patients supplemented with multivitamins and in ones with good SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…Higher rates of severe vitamin D deficiency were previously reported in the literature from Turkey 10,17 . Those prior studies have shown that covered dress style may be an important factor affecting the prevalence of vitamin D deficiency in Muslim populations due to the religious and cultural reasons 10,18. The prevalence of low vitamin D levels was greater in cases which were sampled in winter, in women who had limited access to sunlight, those living in countries at higher latitudes and those with higher skin pigmentation 16,[18][19][20] .…”
Section: Discussionsupporting
confidence: 60%
“…Higher rates of severe vitamin D deficiency were previously reported in the literature from Turkey 10,17 . Those prior studies have shown that covered dress style may be an important factor affecting the prevalence of vitamin D deficiency in Muslim populations due to the religious and cultural reasons 10,18. The prevalence of low vitamin D levels was greater in cases which were sampled in winter, in women who had limited access to sunlight, those living in countries at higher latitudes and those with higher skin pigmentation 16,[18][19][20] .…”
Section: Discussionsupporting
confidence: 60%
“…In a study by Zhao et al (25), the mean level of 25(OH)D in the second trimester was significantly higher than the one in the first trimester and equivalent to the one in the third trimester. Our results are compatible with the recent study which reported high prevalence of severe vitamin D deficiency [25(OH) D<10 ng/mL] (45.6%) among pregnant women in Turkey (26). These findings indicate that vitamin D deficiency is a major health problem in our population as well.…”
Section: Discussionsupporting
confidence: 83%
“…Maternal vitamin D deficiency is common during pregnancy and a widespread public health problem 6 . A high prevalence of vitamin D deficiency has been observed among pregnant women, 7 with prevalence rates varying by ethnicity 8 and sunlight exposure 9 . There is increasing interest in a range of actions of vitamin D in pregnancy, including its effects on placental function and inflammatory response 10 .…”
Section: Introductionmentioning
confidence: 99%